Latin America and the European communities - Jürgen Westphalen (Intereconomics, 1972)
The Latin American reaction to the Common Market of European industrial countries was from the outset marked by scepticism and criticism. It was only recently that new tendencies have been discerned which can perhaps lead to a partial improvement in the relations between EEC and Latin America.
Keywords: 330; Latin America